ANALISIS ALIH KODE SISWA KELAS BAHASA DALAM PEMBELAJARAN DISKUSI DI SEKOLAH MENENGAH ATAS - Siti Hafni Kastella; Hasnani; Sukmawati; Ibrahim, Muliaty (Elite : English and Literature Journal, 2025)
In daily communication, some individuals struggle to express their ideas due to language limitations. As a result, they often resort to code-switching. This phenomenon is also observed among students learning English. This study aimed to analyze the types and functions of code-switching used in English discussion-based learning. A qualitative descriptive method was employed in this research. The participants were 36 eleventh-grade students from the Language Class. Data were collected through observation and interviews. The findings revealed that students used three types of code-switching during discussions: intra-sentential switching, inter-sentential switching, and tag switching. Among these, intra-sentential switching was the most frequently used. Furthermore, the study identified four main functions of code-switching during discussions: emphasizing a point, substituting unknown words, reinforcing requests, and clarifying a point. The analysis indicated that the primary reason for code-switching was students’ limited English vocabulary. Additional linguistic challenges included poor grammar, unclear pronunciation, and a general lack of fluency in English. Consequently, code-switching plays a crucial role in the learning process, as it helps students better understand the material being discussed.